(untitled) (International Journal on Stereo & Immersive Media, 2021)
Using the framework of the tourist gaze to investigate Underwood & Underwood’s Egypt, a 1905 stereoview boxed set with an accompanying book by James Henry Breasted, which is part of a larger collection of stereoview boxed sets by the same company, this paper will define the tourist gaze, provide a brief overview of Underwood & Underwood’s stereoview boxed sets, and examine how Egypt and its cultural heritage are perceived through an outsider’s orientation and set of values as well as the ramifications of this perception. This will be accomplished by focusing on Breasted’s textual depictions of the contemporary Egyptian at the beginning of the twentieth century in the set’s accompanying book, Egypt through the Stereoscope, and included on some of the back sides of the stereoviews in the Egypt set.